Literary modernity and success of selling of the huanuqueñas narrative works (1985 – 2007) - Guillermo Buzzi, Juselino B. (2009)
Literary modernity and success of selling of Huanuqueñas narrative works (1985 - 2007) is a work that argues the success of selling, of the narrative production of the huanuqueños writers Andres Cloud C., Samuel Cárdich A. and Mario Malpartida B. basically, is based on incorporating of modern esthetic and technical resources. This asseveration is corroborated by the constant re-editions of books, such as: Under the shadow of the lemon tree, Bad times, Three histories of love, The old evil of the melancholy, Rolled stories, among others.